Removal and degradation of mixed dye pollutants by integrated adsorption-photocatalysis technique using 2-D MoS2/TiO2 nanocomposite. (September 2021) - Chandrabose, Gauthaman; Dey, Avishek; Gaur, Shivani Singh; Pitchaimuthu, Sudhagar; Jagadeesan, Hema; Braithwaite, N. St John; Selvaraj, Vimalnath; Kumar, Vasant; Krishnamurthy, Satheesh
Abstract: Two-dimensional (2D) Molybdenum disulfide (MoS2 ) has become one of the most exciting areas of research for adsorbents due to its high surface area and abundant active sites. Mainly, 2D MoS2 show promising removal of textile dye pollutants by adsorption process, but it show high affinity for anionic type of dyes, that limits its performance in mixed dye pollutants treatment. Herein, we demonstrate an integrated approach to remove mixed dye pollutants (anionic and cationic) concurrently by combining adsorption and photocatalysis process. We synthesize MoS2 /TiO2 nanocomposites for different weight percentages 2.5, 5, 10, 20, 30 and 50 wt% of pre-synthesized flower-like MoS2 nanoparticle by a two-step hydrothermal method. We demonstrate a new process of two-stage adsorption/photocatalysis using high wt% of MoS2 (Stage-I) and low wt% of MoS2 (Stage-II) nanocomposites. The proposed two-stage integrated adsorption and photocatalysis process using 50% and 2.5% of MoS2 coated TiO2, respectively showed complete removal of methylene blue dye ∼5 times faster than conventional single-stage (adsorption or photocatalysis) water treatment process. Furthermore, the feasibility of the proposed two-stage method in mixed dye pollutants removal (anionic and cationic) testified, which showed excellent performance even in doubling the dye pollutant concentration. This work brings a deeper insight into understanding the morphology and concentration of 2-D MoS2 in MoS2 /TiO2 nanocomposite in tackling mixed dye pollutants and the possibilities of applying in textile dyeing industries wastewater treatment plants. Graphical abstract: Image 1 Highlights: 2-D MoS2 /TiO2 composite synthesized for different weight % of MoS2 . Hybrid adsorption-photocatalysis route showed a high rate of dye pollutants removal. 2-D MoS2 layer lattice widening play a key role in dye pollutants removal. Anionic and cationic mixed dye pollutants removed simultaneously. Two-stage process results 5 times faster dye removal rate than conventional route.